A Family Physician's Journey From the Reservation to the White House. (June 2015) - Helminiak, Clare
<x xml:space="preserve">Abstract</x> There are many challenges faced by family physicians who choose to practice medicine in rural areas with underserved populations. A decision to practice medicine as a physician in the United States Public Health Service, serving American Indians and Alaska Natives, became a fascinating and rewarding journey across the nation and abroad, to the highest levels of government.